Dimensi Politik Dalam Formulasi Kebijakan: Studi Pemekaran Kecamatan Kandang Makmur Wilayah Kota Lhokseumawe - T Sofianus; Fidhia Aruni; Dyah Kuntorini Dwi Angreni; Nurul Kamaly (Journal of Governance and Social Policy, 2023)
At this time the position of the Qanun on the Expansion of the Kandang Makmur District is in the province and awaiting a register number that requires a letter of recommendation from the Minister of Home Affairs. In the discussion process to analyze the problem using political system theory in the formulation of public policy according to David Easton which consists of input, withinput, and output. Researchers chose to use a qualitative approach because a qualitative approach is believed to be able to assist researchers in interpreting and describing the phenomena that occur. The process of expansion of the Kandang Makmur sub-district is full of political elements. The political element is the efforts of Mayor Suaidi Yahya and the Aceh Party to control the legislature of the expansion agenda of the Kandang Makmur sub-district. This is in accordance with the concept that in the policy making process there is the use of interests and power in order to form a policy. So in the formulation process there is a conflict of interest between the executive and the legislature. The Lhokseumawe DPRK as the legislature rationalized the expansion policy of the Kandang Makmur District by providing an alternative policy to the executive as the party proposing the expansion policy of the Kandang Makmur District. So that the next researcher can continue the discussion regarding the implementation of the Qanun for regional expansion in Kandang Makmur District.